The Impact of Diversity, Inclusion and Equity Product Offering and Forecast Bias on Supply Chain Decisions - Xu, Shenghan; Tan, Audrey (International Journal of Economics, Business and Management Studies, 2023)
U.S. demographic change brings new product offerings, production planning, and distribution challenges. While many companies embrace diversity, inclusion, and ethnicity product offering, their practice often renders mixed results, potentially negatively impacting their profitability. We offer an interdisciplinary marketing and supply chain perspective in addressing demand distribution change and its impact on inventory and distribution decisions. In addition, we demonstrate the importance of developing culturally adapted inventory and customer analytics models for manufacturing and supply chain distribution. We examine demand forecast bias in the apparel industry through the product demand distribution analysis at the product size level. We propose supply chain solutions to alleviate the situation by product size re-positioning, distribution channel choice, multistage execution plan, lead time and safety stock, and planning and revenue management approach. We also recognize the potential of addressing the problem by better understanding the consumer behavior change process and allowing a more extended period of marketing campaigns. In the apparel industry, the planning and supply chain decisions assume product demand follows a normal distribution. However, our research found that the demand distribution is highly skewed with significant kurtosis. Therefore, during the planning stage, inventory policy must be adjusted to count for the bias in the demand distribution. Moreover, managers can orchestrate other supply chain and marketing solutions such as centralized operation, leading time and safety stock trade-offs, and more extended marketing campaigns to match supply and demand better. Our work offers some analytical and practical approaches to increase a better supply and demand match.